Lichen sclerosus and hidradenitis suppurativa: Two case reports of a new possible association. (19th August 2020) - Moliterni, Elisa; Miraglia, Emanuele; Iacovino, Chiara; Bianchini, Daniela; Giustini, Sandra
Abstract: We report the cases of two women affected by lichen sclerosus also having clinical signs of hidradenitis suppurativa. Lichen sclerosus is a chronic autoimmune disease, in which activated fibroblasts produce significantly altered collagen leading to fibrosis Hidradenitis suppurativa is a chronic relapsing inflammatory disease affecting folliculopilosebaceous unit and apocrine gland, which lesions are nodules and abscesses. The association between lichen sclerosus and autoimmune disorders is well known, but not the one with hidradenitis suppurativa. We present two case reports of these unusual comorbidities.